Eddy Current Method for Testing of Metals under Simultaneous Exposure to Radiation and Hydrogenation; Advanced Materials Research : Radiation and nuclear techniques in material science; Vol. 1084 : Physical-Technical Problems of Nuclear Science, Energy Generation, and Power Industry (PTPAI -2014) - Larionov V. V. Vitaliy Vasilyevich (Materials Science and Technologies, 2015)
Title screen